Faktor-Faktor yang Memengaruhi Remaja Buddhis Dusun Candi, Desa Candigaron, Kecamatan Sumowono, Kabupaten Semarang Putus Sekolah - Annanda Widya Putra; Kustiani Kustiani; Kiryono Kiryono (Jurnal Maitreyawira, 2022)
This study aims to describe the factors that influence Buddhist youth in Candi Village, Candigaron Village, Sumowono District, Semarang Regency. This research uses a descriptive qualitative method. The research data were collected by interview, observation, and documentation. The validity of the data the was tested by diligent observation, triangulation, and member check. Data analysis is based on the Miles and Huberman model consisting of data collection, data reduction, data presentation, and drawing conclusions, as well as verification. The results of this study indicate that the factors that cause dropout in Buddhist adolescents in Dusun Candi consist of two factors, namely internal and external. The internal factors are factors that come from within the youth themselves, such as the is low motivation/interest to goto school. External factors are factors that come from outside the youth, such as economic, socio-cultural and geographical limitations. Furthermore, the effects of Buddhist dropouts are included in the four mental powers (iddhipada) consisting of chanda,viriya, citta, and vimaṁsā.